Hylarana Raniceps (White-lipped Frog). Predation - Das, Indraneil; Riehl, Torben; Haas, Alexander (Society for the Study of Amphibians and Reptiles, 2008)
We relate herein an observation of the predation of a Hylarana raniceps metamorph by a spider. H. raniceps is a common species in the lowlands of Bornean dipterocarp forests. In March 2007, we observed a “fishing spider” of the species Thalassius cf. albocinctus (Doleschall, 1859) at a alluvial pond off Headhunters’ Trail, near Camp 5 (04.139056°N, 114.899944°E), Gunung Mulu National Park, Sarawak, East Malaysia (Borneo), with a metamorph of H. raniceps as prey.